Fiscal easing in local governments facing potential merger: Visible in budgets or hidden in overruns?. (15th September 2021) - Askim, Jostein; Houlberg, Kurt; Klausen, Jan Erling
Abstract: Mergers incentivize local governments to ease their fiscal policies before the merger is implemented. This incentive is powerful: it is known that local governments start easing fiscal policies even before they know for sure that a merger will occur and even if merging is what they want. Based on a study of Norwegian municipalities, this article shows that irrespective of whether local governments face certain or potential mergers, their fiscal easing is manifested primarily in budget overruns rather than candidly documented in budgets. Among local governments facing a potential merger, unwilling governments ease their fiscal policies more than willing ones do and to a larger extent apply a concealment strategy.